Model Teoritis Adopsi Inovasi Pertanian: Integrasi Pendekatan Perilaku Petani - Filya Hidayati; Rahmat Syahni; Irfan Suliansyah; Hery Bachrizal Tanjung (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
This study investigates the theoretical frameworks of innovation adoption and farmer behavior within the context of Indonesian agriculture, with the aim of exploring their implications for the advancement of the agricultural sector. Theories of innovation adoption and farmer behavior provide essential lenses through which the dynamics of technological uptake and decision-making processes in agriculture can be understood. Employing a literature review methodology, this paper analyzes a wide range of sources, including peer-reviewed journals, reports, academic textbooks, and recent statistical data relevant to both theoretical models. The analysis reveals that the adoption of agricultural technological innovations is shaped by a combination of internal factors—such as farmer demographics (age, education, experience), attitudes toward risk, and perceptions of innovation—and external factors, such as access to information, financial resources, and institutional support. A thorough understanding of these elements is expected to serve as a strong basis for developing effective strategies and policies aimed at enhancing the adoption of agricultural technologies in Indonesia.